Acquisition of C3d‐Binding Activity by De Novo Donor‐Specific HLA Antibodies Correlates With Graft Loss in Nonsensitized Pediatric Kidney Recipients. Issue 7 (16th February 2016) - Comoli, P.; Cioni, M.; Tagliamacco, A.; Quartuccio, G.; Innocente, A.; Fontana, I.; Trivelli, A.; Magnasco, A.; Nocco, A.; Klersy, C.; Rubert, L.; Ramondetta, M.; et al.
Abstract : Alloantibody‐mediated graft injury is a major cause of kidney dysfunction and loss. The complement‐binding ability of de novo donor‐specific antibodies ( dn DSAs) has been suggested as a prognostic tool to stratify patients for clinical risk. In this study, we analyzed posttransplant kinetics of complement‐fixing dn DSAs and their role in antibody‐mediated rejection development and graft loss. A total of 114 pediatric nonsensitized recipients of first kidney allograft were periodically monitored for dn DSAs using flow bead assays, followed by C3d and C1q assay in case of positivity. Overall, 39 patients developed dn DSAs, which were C1q + and C3d + in 25 and nine patients, respectively. At follow‐up, progressive acquisition over time of dn DSA C1q and C3d binding ability, within the same antigenic specificity, was observed, paralleled by an increase in mean fluorescence intensity that correlated with clinical outcome. C3d‐fixing dn DSAs were better fit to stratify graft loss risk when the different dn DSA categories were evaluated in combined models because the 10‐year graft survival probability was lower in patients with C3d‐binding dn DSA than in those without dn DSAs or with C1q + /C3d − or non‐complement‐binding dn DSAs (40% vs. 94%, 100%, and 100%, respectively). Based on the kinetics profile, we favor dn DSA removal or modulation at first confirmed positivity, with treatment intensification guided by dn DSA biological characteristics. Abstract : In this longitudinal study of renal transplant recipients, the authors demonstrate that patients with de novo donor‐specific HLA antibodies capable of C3d binding are more likely to develop antibody‐mediated rejection and graft loss, and describe the dynamic and progressive phenomenon of complement‐binding ability acquisition.